2020
DOI: 10.1098/rspb.2020.1390
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide and resource stressors additively impair wild bee reproduction

Abstract: Bees and other beneficial insects experience multiple stressors within agricultural landscapes that act together to impact their health and diminish their ability to deliver the ecosystem services on which human food supplies depend. Disentangling the effects of coupled stressors is a primary challenge for understanding how to promote their populations and ensure robust pollination and other ecosystem services. We used a crossed design to quantify the individual and combined effects of food resource limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 58 publications
0
98
0
Order By: Relevance
“…While no significant differences in feeding behavior and relative daily consumption were observed across treatments, a significant positive correlation between increased food intake during the first 10 days (i.e., exposure period) and longevity was observed for all treatments and controls. While we have no data to support that fitness may be affected, previous studies using comparable concentrations of neonicotinoid insecticides have revealed a reduced reproduction, but no effects on adult survival [ 10 , 11 ]. Therefore, we postulate that exposed bees may opt for improved longevity over reproductive capacities (i.e., fitness) [ 28 , 51 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…While no significant differences in feeding behavior and relative daily consumption were observed across treatments, a significant positive correlation between increased food intake during the first 10 days (i.e., exposure period) and longevity was observed for all treatments and controls. While we have no data to support that fitness may be affected, previous studies using comparable concentrations of neonicotinoid insecticides have revealed a reduced reproduction, but no effects on adult survival [ 10 , 11 ]. Therefore, we postulate that exposed bees may opt for improved longevity over reproductive capacities (i.e., fitness) [ 28 , 51 ].…”
Section: Discussionmentioning
confidence: 62%
“…Irrespective of the underlying mechanism, the consequence of increased survival is likely to trade-off for other physiological factors [ 69 ], possibly affecting fitness [ 30 , 63 ]. Indeed, ample evidence exists from the laboratory and the field indicating such trade-off scenarios, wherein pesticide exposure decreased fitness parameters while not necessarily affecting survival [ 10 , 11 , 70 ]. Undoubtedly, our experiment would have benefited from directly measuring detoxification capacities and fitness (i.e., production of offspring) or sublethal parameters that adequately reflect fitness (i.e., ovary development in females or sperm quality in males) to confirm a possible trade-off scenario in solitary bees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this substantially reduces average offspring survival (e.g., if offspring survival falls over a fitness cliff), then adult exposure to stressors can result in a large indirect cost in terms of both offspring and adult fitness. For example, blue orchard bees (Osmia lignaria ) exposed to resource limitation and the pesticide imidacloprid suffered an additive reduction in reproductive fitness via a lowered probability of successful nesting and a reduced number of offspring produced (Stuligross & Williams 2020). Additionally, offspring sex ratios became male biased, increasing the likelihood of further reductions in reproductive fitness in the future (Stuligross & Williams 2020).…”
Section: Trade-off 3: Energy Allocation Between Stressors and Life-himentioning
confidence: 99%
“…The few studies addressing the impact of neonicotinoid exposure on reproductive physiology have primarily focused on honey bees or female solitary bees (Williams et al ., 2015; Chaimanee et al ., 2016; Straub et al ., 2016; Wu‐Smart & Spivak, 2018; Azpiazu et al ., 2019), whereas data for male wild bees are currently lacking. However, impaired male reproductive physiology may be a key mechanistic explanation for observed severe negative consequences of field‐realistic neonicotinoid exposure on solitary bee fitness and population density (Sandrock et al ., 2014; Rundlöf et al ., 2015; Stuligross & Williams, 2020).…”
Section: Introductionmentioning
confidence: 99%